Analysis of The Influence of Zakat on Economic Growth in Five Districts/Cities of Banten Province - Nursaman Nursaman; Surya Darma Syam (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2025)
ABSTRACT: The purpose of this study is to analyze the influence of zakat on economic growth in five districts/cities in Banten Province in 2017-2021. The research method used in this article is a descriptive verification method with a quantitative quantitative approach. This research can also be verified, which means that it will be tested using analytical tools to prove the relationship between variables in the study and in the form of proof (accepted or rejected) through statistical calculations. The results of the study are based on path analysis with SmartPLS application statistics version 4.0. concludes that there is a positive and significant direct influence of the zakat acquisition variable (X) on the economic growth variable (Y). This can show the results of data processing that the T-Statistic is 10,762 (> 1,674) and the P value is 0.000 (< 0.05). The result can be concluded that the Ha hypothesis is accepted and Ho is rejected. This means that there is a direct positive and significant influence on the level of zakat collection on economic growth. Recommendation: to increase the acquisition of zakat, policy makers (government) to make a law on the collection of zakat for citizens who are obliged to zakat, as done by the Prophet PBUH and his followers as state fiscals.